Lateral Orbitotomy for Cavernous Malformation: A Case Report with Technical Consideration (Bangladesh Journal of Neurosurgery, 2020)
Cavernoma is benign tumour of the orbit. It results in proptosis, visual disturbance, diplopia and ptosis of the eye. It is amenable to surgery and this results in complete after surgical removal without recurrence. We report a case of right orbital cavernoma in a female, who presented with non-pulsatile painless proptosis, slight ptosis and double vision while looking at the right side. Her MRI revealed that she had a cavernoma of the right orbit. She was operated by the lateral orbitotomy. This easily removed the tumour, cosmetically acceptable and she became symptom free.Bang. J Neurosurgery 2020; 10(1): 102-105